PERFORMANCE MEASUREMENT IN THE HELPFUL ASPECT BETWEEN LOCAL GOVERNMENT POLICIESBY GOVERNMENT POLICIES (Performance Evaluation Study of Local Government Implementation (EKPPD) Pontianak Year 2014) - NELLA LENNY HERIYANI, S.H., M.K.N NPM. A2021151093, Jurnal Mahasiswa s2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses about the performance measurement on alignment aspect between local government policy and government policy (Study of Performance Evaluation of Local Government Implementation (EKPPD) Pontianak Year 2014). From the result of this thesis research, it is concluded that Performance Measurement On Aspect of Alignment Between Local Government Policy With Government Policy Related to Performance Evaluation of Local Government (EKPPD) Pontianak City Year 2014. Bureaucracy in Pontianak City area is essentially to change the governance of development towards good governance (good govenance). Good governance is characterized by, among other things, high levels of performance, public accountability, transparency, efficiency, effectiveness, cleansing of corruption, collusion and nepotism. To support good governance, a good performance measurement system is needed. This performance measurement system will integrate the process of improving performance through the planning startup phase until its performance evaluation. A good performance measurement system will be beneficial for a variety of things that can be used to apply reward and punishment systems, evaluate the efficiency, effectiveness and economics of programs and activities, improve performance, and others. Factors affecting alignment performance between local government policies With the government policy related to the Performance Evaluation of Local Government (EKPPD) Pontianak Year 2014 is the existence of several factors that influence the performance of the local government of Pontianak City, including about the characteristics of Pontianak local government that includes organizational culture, organizational structure, and external environment.In addition, from the results of the study found that the size (size) of Pontianak, leverage, and intergovernmentaltr ansfer have significant effect on the performance of the local government of Pontianak City, but the legislative or DPRD size has no significant effect on the performance of the Pontianak Municipal Government. The size of Pontianak Municipal Government as measured by natural logs (ln) of Pontianak local government assets, the level of regional wealth as measured by PAD, the level of dependence of local government on central government, regional expenditure, and BPK audit findings have a significant effect on the performance scores of Pontianak Municipality. Efforts that should be done by the city government pontianak in an effort to improve performance in relation to the Performance Evaluation of Local Government (EKPPD) Pontianak Year 2014 is Pontianak Government Institution Performance Pontianak get predicate B in the assessment of Performance Accountability Accountability Government Agencies (LAKIP) .Pontianak City is the only city of all districts / cities in West Kalimantan who received the title B in the assessment of LAKIP with the achievement of B in the assessment of this LAKIP, an increase from the previous. Keywords: Performance Measurement, Policy, Local Government, Government Polic ABSTRAK Tesis ini membahas tentang pengukuran kinerja pada aspek keselarasan antara kebijakan pemerintah daerah dengan kebijakan pemerintah (Studi Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD) Kota Pontianak Tahun 2014).. Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Pengukuran Kinerja Pada Aspek Keselarasan Antara Kebijakan Pemerintah Daerah Dengan Kebijakan Pemerintah Terkait Dengan Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD) Kota Pontianak Tahun 2014. Birokrasi di daerah Kota Pontianak intinya adalah melakukan perubahan tata laksana pembangunan menuju pemerintahan yang baik (good govenance). Kepemerintahan yang baik ditandai antara lain dengan tingginya tingkat kinerja, adanya akuntabilitas publik, transparansi, efisiensi, efektivitas, bersih dari korupsi, kolusi, dan nepotisme Untuk mendukung terwujudnya kepemerintahan yang baik tentunya diperlukan adanya sistem pengukuran kinerja yang baik. Sistem pengukuran kinerja ini akan mengintegrasikan proses peningkatan kinerja melalui tahap mulai perencanaan sampai dengan evaluasi capaiannya. Sistem pengukuran kinerja yang baik akan bermanfaat untuk berbagai hal diantaranya dapat digunakan untuk menerapkan sistem reward and punishment, mengevaluasi efisiensi, efektivitas, dan ekonomis program dan kegiatan, meningkatkan kinerja, dan lain-lain. Faktor-faktor yang mempengaruhi kinerja keselarasan antara kebijakan pemerintah daerah dengan kebijakan pemerintah terkait dengan Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD) Kota Pontianak Tahun 2014 ialah adanya beberapa faktor yang mempengaruhi kinerja pemerintah daerah Kota Pontianak, di antaranya tentang karakteristik pemda Kota Pontianak yang meliputi budaya organisasi, struktur organisasi, dan lingkungan eksternal. Selain itu dari hasil penelitian menemukan bahwa ukuran (size) pemerintah daerah Kota Pontianak, leverage, dan intergovernmentaltr ansfer berpengaruh signifikan terhadap kinerja pemerintah daerah Kota Pontianak, tetapi ukuran legislatif atau DPRD tidak berpengaruh signifikan terhadap kinerja Pemda Kota Pontianak. ukuran pemda Kota Pontianak yang diukur dengan log natural (ln) asset pemda Kota Pontianak, tingkat kekayaan daerah yang diukur dengan PAD, tingkat ketergantungan pemerintah daerah terhadap pemerintah pusat, belanja daerah, dan temuan audit BPK berpengaruh signifikan terhadap skor kinerja pemda Kota Pontianak. Upaya-upaya yang seharusnya dilakukan oleh pemerintah kota pontianak dalam dalam upaya peningkatan kinerja dalam kaitannya dengan Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD) Kota Pontianak Tahun 2014 ialah Kinerja Instansi Pemerintahan Pontianak Kota Pontianak mendapat predikat B dalam penilaian Laporan Akuntabilitas Kinerja Instansi Pemerintahan (LAKIP). Kota Pontianak merupakan satu-satunya kota dari seluruh kabupaten/kota se-Kalimantan Barat yang menerima predikat B dalam penilaian LAKIP tersebut dengan diraihnya predikat B dalam penilaian LAKIP ini, ada peningkatan dari sebelumnya